A Girardian Approach to LaVeyan Satanism: Theological Perspectives. (February 2021) - Andrade, Gabriel
This article addresses some convergences in Rene Girard and Anton LaVey's understandings of Satan. Rene Girard understood Satan as the representation of both mimetic desire and the scapegoat mechanism, both of which have detrimental influences on human culture. In that sense, in continuation with Christian orthodoxy, Girard did not find any positive aspect in Satanism. By contrast, Anton LaVey had a more positive approach to Satan. LaVey was an unsophisticated Nietzschean, who nevertheless understood well that the German philosopher's views were not dissimilar to what Satan represents. Rene Girard's understanding of who (or what) Satan is, makes this clearer.